Structural and mechanistic insights into the neurotensin receptor - Grisshammer, Reinhard (Henry Stewart Talks, 2019)
G protein-coupled receptors, Neurotensin receptor, Peptide agonist neurotensin tools for crystallization of membrane proteins, Conformational thermostabilization, Crystal structure of NTSR1-GW5, Binding mode of neurotensin, Crystal structures of NTSR1-ELF & NTSR1-LF-prerequisites for G protein activation, Crystal structure of NTSR1-EL, Constitutive activity, Molecular dynamics simulations